Turbulent convection in a solar air heater channel with baffles/winglets - Skullong, S.; Tamna, S.; Promvonge, P. (My University, 2014)
The paper presents a study on heat transfer, friction loss and thermal performance behaviors in a solar air heater channel fitted with baffle turbulator (BT) or triangular-winglet vortex generator (WVG) at various winglet/baffle to channel-height or blockage ratios (BR=b/H=0.1 0.15 and 0.2). The BT and the WVG were placed only on the upper wall/absorber plate of the test channel at a single axial pitch ratio (PR=P1/H=4). The investigation is performed for the Reynolds number ranging from 5400 to 23,000. The upper wall of the channel is uniformly heated as a constant heat flux while the rests are covered with thermal insulations to reduce heat loss to surroundings. The BT and the WVG were, respectively, mounted with the attack angle of 90° and 60° relative to main flow direction. The experimental results indicate that the absorber plate with the WVGs provides considerable improvement of the heat transfer rate over the smooth channel around 4.29 to 4.33 times for BR=0.2. The use of the WVG placed on the absorber plate leads to the highest heat transfer rate, friction factor and thermal performance in comparison with the BT and the smooth channel. The WVG at BR=0.2 provides the maximum thermal performance up to 1.61. Thus, because of stronger vortex flow, the WVG at largest BR becomes influential upon the heat transfer and thermal performance enhancement. © 2014 Asian Institute of Technology.
Keywords: Absorber plate; Heat transfer; Thermal performance; Vortex flow; Winglet